Implementation of Mass Drug Administration for Lymphatic Filariasis in Madagascar: The Progress, Effectiveness and Financial Savings of Integrating into an Existing Polio Campaign - Mandrosovololona V; Rasoamihanta P; Djawe K; Mupfasoni D; Andriamino B; Rakotonavalona R; Bakajika D; Ratsimbasoa AC; Kirigia J; Musango L (Research and Reports in Tropical Medicine)
Vatsiharizandry Mandrosovololona,1 Patricia Rasoamihanta,1 Kpandja Djawe,1 Denise Mupfasoni,2 Brusa Andriamino,3 Rivomalala Rakotonavalona,3 Didier Bakajika,4 Arsène Claude Ratsimbasoa,5 Joses Kirigia,6 Laurent Musango1 1Madagascar Country Office, World Health Organization, Antananarivo, Madagascar; 2Department of Control of Neglected Tropical Diseases, World Health Organization, Geneva, Switzerland; 3Ministry of Public Health, Antananarivo, Madagascar; 4Expanded Special Project for Elimination of NTD (ESPEN), World Health Organization Regional Office for Africa, Brazzaville, Congo; 5Faculty of Medicine, University De Fianarantsoa, Antananarivo, Madagascar; 6African Sustainable Development Research Consortium (ASDRC), Nairobi, KenyaCorrespondence: Laurent Musango, WHO Country Office, P.O. Box 362, Antananarivo, 101, Madagascar, Email musangol@who.intIntroduction: This paper presents (a) the progress made towards achieving the 2023 Lymphatic Filariasis (LF) Mass Drug Administration (MDA) campaign goals, (b) the estimated financial savings resulting from integrating LF MDA into Polio immunization campaigns, and (c) the best practices, challenges, and recommendations.Methods: In 2023, 21,336,057 people in 83 districts were affected by LF and required Preventive Chemotherapy (PC). The National NTD Control Programme (NTDCP) conducted three phases of LF MDA campaigns in those districts. In the first phase, 24 districts received triple therapy of Ivermectin, Diethylcarbamazine, and Albendazole (IDA), while the remaining 59 districts continued to receive dual therapy of Diethylcarbamazine and Albendazole (DA) as before. The first phase (15 districts) was not integrated, while the second phase (61 districts) was conducted simultaneously with the Polio Supplementary Immunization Activities (SIA) fourth round. The third phase (7 districts) was combined with periodic intensification of routine immunization (PIRI) and vitamin A supplementation.Results: In Phases 2 and 3, the campaign covered 99.97% of the targeted 12,208 villages, meaning only three villages remained untreated. In contrast, Phase 1 covered all the targeted 2,847 villages, attaining 100% geographic coverage. The 68 districts (Phase 2 and 3) that implemented an integrated approach attained an average therapeutic coverage of 76.6% (STDEV=8.3) compared to 73.2% (STDEV=6.7) among the 15 districts (Phase 1) that conducted MDA for LF without integration. The p-values for geographical and therapeutic coverage were below the significance level of 0.05, leading to the conclusion that the average geographic and therapeutic coverages for districts implementing LF MDA with and without integration into Polio immunization campaigns differed significantly. Integrating the LF MDA campaign into the Polio SIA and PIRI campaigns saved US$1,431,203.Conclusion: Incorporating LF MDA into polio immunization campaigns can improve financial efficiency and effectiveness in meeting the objectives of LF programs.Keywords: cost effectiveness, integration, mass drug administration, financial savings